Primary Versus Secondary Radiotherapy for Heterotopic Ossification Prevention About the Elbow. Issue 2 (February 2022) - Geller, Joseph S.; Allegra, Paul R.; Seldon, Crystal S.; Spieler, Benjamin O.; Cohen, Lara L.; Barnhill, Spencer W.; Huntley, Samuel R.; De La Zerda, Alberto; Samuels, Stuart; Wang, Lora; Isrow, Derek; Wolfson, Aaron H.; et al.
Abstract : Objectives: To examine the efficacy and safety of radiotherapy for the prevention of heterotopic ossification (HO) about the elbow. Design: Retrospective chart review. Setting: Level 1 trauma center. Patients/Participants: Two hundred and twenty-nine patients who received prophylactic radiotherapy (XRT) over a 15-year period were identified. Patients were included if they received XRT to the elbow joint and had at least 12 weeks of follow-up after XRT. Fifty-four patients were ultimately included. Intervention: All patients were treated with a single dose of 7 Gy. Ninety-eight percentage of patients received XRT within 24 hours after surgery, and all patients received XRT within 72 hours after surgery. Main Outcomes Measurements: The primary study measures evaluated were the presence or absence of clinically symptomatic HO and the presence of radiographic HO after XRT to the elbow joint. Results: Eighteen patients were treated with XRT after a traumatic injury requiring surgery (primary prophylaxis), and 36 were treated with XRT after excision surgery to remove HO which had already formed (secondary prophylaxis). In the primary cohort, 16.7% developed symptomatic HO after XRT and 11.1% required surgery to resect the heterotopic bone. In the secondary cohort, 11.1% developed symptomatic HO after surgery and XRT and 5.5% required resection surgery. No secondary malignancies were identified. Conclusions: Our findings suggest that XRT for elbow HO may be safe and effective for both primary and secondary HO. XRT for HO was not shown to be associated with radiation-induced sarcoma in this series, at least in the short term. Further study in a large patient population with extended follow-up is required to better characterize populations at high risk for development of HO and secondary malignancy. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.